Ni nanoparticle reinforced porous electromagnetic shielding film and preparation method thereof

Through the synergistic effect of Ni nanoparticles and Ti3C2Tx MXene and porous structure optimization, a Ni/Ti3C2Tx MXene porous composite film was prepared, solving the problem of low electromagnetic shielding performance of Ti3C2Tx MXene, achieving efficient electromagnetic shielding effect and conductivity improvement.

CN119233616AActive Publication Date: 2024-12-31XIAN UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411341373.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing Ti3C2Tx MXene electromagnetic shielding material has low electromagnetic shielding performance due to its high intrinsic conductivity, poor impedance matching and single loss mechanism, which cannot meet commercial requirements.

Method used

Through the synergistic effect of Ni nanoparticles and Ti3C2Tx MXene, combined with the impedance matching regulation of the porous structure, Ni/Ti3C2Tx MXene porous composite film was prepared, and PMMA@Ni/Ti3C2Tx MXene nanospheres were prepared by template method and hydrothermal method, and then heat treatment and vacuum Suction filtration to obtain a porous composite film.

Benefits of technology

It significantly improves the electromagnetic shielding performance of Ti3C2Tx MXene, enhances magnetic loss capability and impedance matching, achieves efficient electromagnetic shielding effect, improves conductivity, and reaches 70.7dB to 77.4dB, exceeding the performance requirements of commercial materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119233616A_ABST
    Figure CN119233616A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Ni nanoparticle reinforced porous electromagnetic shielding film. The preparation method specifically comprises the following steps: step 1, preparing PMMA coated Ni / Ti < 3 > C < 2 > T < x > MXene nanospheres; and step 2, preparing the Ni / Ti < 3 > C < 2 > T < x > MXene porous composite film. The invention further discloses a Ni nanoparticle reinforced porous electromagnetic shielding film, and the problem that the electromagnetic shielding performance of single Ti < 3 > C < 2 > T < x > MXene is low is solved through the synergistic effect of Ni nanoparticles and Ti < 3 > C < 2 > T < x > MXene in the performance aspect and impedance matching regulation and control of a porous structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new materials, and in particular relates to a Ni nanoparticle-enhanced porous electromagnetic shielding film, and also relates to a preparation method of the Ni nanoparticle-enhanced porous electromagnetic shielding film. Background Art

[0002] Electromagnetic shielding materials are functional materials that can shield electromagnetic waves to protect electronic devices and equipment. Currently, commercial electromagnetic shielding materials are mainly metals and their alloys, which have problems such as high density, poor corrosion resistance and difficult processing, which limits their application. x MXene materials have the characteristics of good conductivity, light weight, large specific surface area and high mechanical strength. Thanks to the rich internal carriers, Ti3C2T x MXene exhibits metal-like conductivity, which is very beneficial for electromagnetic shielding dominated by dielectric loss. x There are a large number of defects and terminal groups on the surface of MXene, which can easily lead to uneven electron distribution. Under the action of an external field, the aggregated electrons will form dipoles, thereby generating polarization loss and attenuating electromagnetic waves.

[0003] However, Ti3C2T is limited by factors such as high intrinsic conductivity, poor impedance matching and single loss mechanism. x The electromagnetic shielding performance of MXene is still somewhat far from commercial requirements. Summary of the invention

[0004] The first object of the present invention is to provide a Ni nanoparticle-reinforced porous electromagnetic shielding film, wherein Ni nanoparticles and Ti3C2T x The synergistic effect of MXene in performance and the impedance matching regulation of the porous structure solve the problem of single Ti3C2T x The problem of low electromagnetic shielding performance of MXene.

[0005] The second object of the present invention is to provide a method for preparing a Ni nanoparticle-reinforced porous electromagnetic shielding film. The method is simple and easy to operate. The prepared film is prepared by combining Ni nanoparticles with Ti3C2T x The synergistic effect of MXene in performance and the impedance matching regulation of the porous structure solve the problem of single Ti3C2T x The problem of low electromagnetic shielding performance of MXene.

[0006] The first technical solution adopted by the present invention is a method for preparing a Ni nanoparticle-reinforced porous electromagnetic shielding film, which specifically comprises the following steps:

[0007] Step 1, PMMA@Ni / Ti3C2T xPreparation of MXene nanospheres;

[0008] Step 2, Ni / Ti3C2T x Preparation of MXene porous composite films.

[0009] The present invention is also characterized in that:

[0010] Step 1 is implemented as follows:

[0011] Step 1.1, preparation of PMMA / Ti3C2T by template method x MXene nanosphere mixed solution:

[0012] First, a PMMA nanosphere dispersion with a concentration of 10 mg / mL to 20 mg / mL was prepared, and ultrasonic treatment was performed for 1 h to 3 h. Then, a Ti3C2T x MXene nanosheet dispersion; Ti3C2T x The MXene nanosheet dispersion was slowly dripped into the PMMA nanosphere dispersion, and PMMA and Ti3C2T in the mixed solution x The mass ratio of MXene nanosheets was 1:1-2, and the mixed solution was ultrasonically treated in an ice bath for 20-40 min and magnetically stirred for 2-5 h to obtain PMMA / Ti3C2T x MXene nanosphere mixed solution;

[0013] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti3C2T x MXene nanospheres:

[0014] Dissolve NiCl2·6H2O in anhydrous ethanol to prepare a solution with a concentration of 0.6 mg / mL to 4 mg / mL, treat with ultrasound for 20 min to 40 min to mix evenly, and then drop the solution into the PMMA / Ti3C2T x In the MXene nanosheet mixed solution, after the solution is added, continue to stir for 1h to 3h to obtain a mixed solution A, add NaOH to the mixed solution A, the concentration of NaOH in the mixed solution A is 0.5g / mL to 0.8g / mL, and then stir in an ice bath for 20min to 40min to fully dissolve it to obtain a mixed solution B; then add N2H4·H2O to the mixed solution B, the volume ratio of N2H4·H2O to anhydrous ethanol is 1:1 to 3, stir for 20min to 40min to obtain a mixed solution C, put the fully stirred mixed solution C into a stainless steel reactor, and then carry out a hydrothermal reaction in a drying oven at 120℃ to 150℃ for 10h to 15h. After the reaction is completed, wash and dry to obtain black PMMA@Ni / Ti3C2T xMXene nanosphere powder.

[0015] In step 1.1: the size of PMMA nanospheres is 200nm~600nm; Ti3C2T x MXene nanosheets were prepared from Ti3AlC2 powder by chemical etching, with HCl / LiF as the etchant.

[0016] Step 2 is implemented as follows:

[0017] Take the concentration of 2mg / mL~4mg / mL Ti3C2T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti3C2T was prepared according to step 1.2. x MXene nanosphere powder was dissolved in deionized water to prepare a dispersion with a concentration of 8 mg / mL to 16 mg / mL, and then 8 mg / mL to 16 mg / mL of PMMA@Ni / Ti3C2T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer of water was drained, Ti3C2T x The MXene nanosheet dispersion was filtered for the third layer; the volume ratio of the three-layer filtrate was 1:1 to 4:1, and the entire film was taken out with the filter membrane after the water was drained, and then separated from the filter membrane after vacuum freeze drying for 20h to 28h, and PMMA@Ni / Ti3C2T x The MXene film was placed in a quartz boat, put into a tube furnace, and heated to 400°C-600°C at a heating rate of 2°C / min-5°C / min under Ar gas protection, and kept warm for 1h-3h. After cooling to room temperature, Ni / Ti3C2T x MXene porous composite film.

[0018] The second technical solution adopted by the present invention is that the Ni nanoparticle-reinforced porous electromagnetic shielding film is prepared by the above method.

[0019] The beneficial effects of the present invention are:

[0020] (1) The method of the present invention prepares PMMA / Ti3C2T by template method x MXene nanospheres, and then PMMA@Ni / Ti3C2T was prepared by hydrothermal method. x MXene nanospheres, PMMA@Ni / Ti3C2T prepared above x MXene nanospheres were introduced into the film material, and Ni / Ti3C2T with both porous structure and magnetic-dielectric loss capacity was obtained by heat treatment, vacuum-assisted filtration and freeze drying.x MXene porous film. At the same time, the present invention prepares Ni / Ti3C2T x The method of preparing MXene porous films has the characteristics of simple process flow.

[0021] (2) The method of the present invention solves the problems of high density, poor corrosion resistance and difficult processing of the currently commercial electromagnetic shielding materials mainly composed of metals and their alloys. In addition, by using Ni nanoparticles, Ti3C2T x The synergistic effect of MXene performance and the hollow structure optimized impedance matching solves the problem of Ti3C2T x The problem of low electromagnetic shielding performance of MXene.

[0022] (3) The thin film of the present invention is obtained by x MXene combined with magnetic Ni nanoparticles can endow Ti3C2T x The magnetic loss capacity of MXene materials is combined with the design of porous structures to optimize impedance matching, and the electromagnetic shielding performance is enhanced through the synergistic optimization of performance and structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The Ni / Ti3C2T prepared in Example 1 x MXene porous composite film PMMA@Ni / Ti3C2T x XRD pattern of MXene nanospheres;

[0024] Figure 2 PMMA@Ni / Ti3C2T prepared in Example 1 x TEM image of MXene nanospheres;

[0025] Figure 3 The Ni / Ti3C2T prepared in Example 1 x SEM image of the cross section of MXene porous composite film;

[0026] Figure 4 for Figure 3 Magnified image of area “A” in the middle;

[0027] Figure 5 Ni / Ti3C2T x Element distribution image of C element in MXene porous composite film;

[0028] Figure 6 Ni / Ti3C2T x Element distribution image of Ti element in MXene porous composite film;

[0029] Figure 7 Ni / Ti3C2T x Element distribution image of Ni element in MXene porous composite film. DETAILED DESCRIPTION

[0030] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0031] The present invention provides a method for preparing a Ni nanoparticle-reinforced porous electromagnetic shielding film, which specifically comprises the following steps:

[0032] Step 1, PMMA@Ni / Ti3C2T x Preparation of MXene nanospheres;

[0033] Step 1 is implemented as follows:

[0034] Step 1.1, preparation of PMMA / Ti3C2T by template method x MXene nanosphere mixed solution:

[0035] First, a PMMA nanosphere dispersion with a concentration of 10 mg / mL to 20 mg / mL was prepared, and ultrasonic treatment was performed for 1 h to 3 h. Then, a Ti3C2T x MXene nanosheet dispersion; Ti3C2T x The MXene nanosheet dispersion was slowly dripped into the PMMA nanosphere dispersion, and PMMA and Ti3C2T in the mixed solution x The mass ratio of MXene nanosheets was 1:1-2, and the mixed solution was ultrasonically treated in an ice bath for 20-40 min and magnetically stirred for 2-5 h to obtain PMMA / Ti3C2T x MXene nanosphere mixed solution;

[0036] In step 1.1: the size of PMMA nanospheres is 200nm~600nm; Ti3C2T x MXene nanosheets were prepared from Ti3AlC2 powder by chemical etching, with HCl / LiF as the etchant.

[0037] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti3C2T x MXene nanospheres:

[0038] Dissolve NiCl2·6H2O in anhydrous ethanol to prepare a solution with a concentration of 0.6 mg / mL to 4 mg / mL, treat with ultrasound for 20 min to 40 min to mix evenly, and then drop the solution into the PMMA / Ti3C2T xIn the MXene nanosheet mixed solution, after the solution is added, continue to stir for 1h to 3h to obtain a mixed solution A, add NaOH to the mixed solution A, the concentration of NaOH in the mixed solution A is 0.5g / mL to 0.8g / mL, and then stir in an ice bath for 20min to 40min to fully dissolve it to obtain a mixed solution B; then quickly add N2H4·H2O to the mixed solution B, the volume ratio of N2H4·H2O to anhydrous ethanol is 1:1 to 3, stir for 20min to 40min to obtain a mixed solution C, put the fully stirred mixed solution C into a stainless steel reactor, and then carry out a hydrothermal reaction in a drying oven at 120℃ to 150℃ for 10h to 15h. After the reaction is completed, wash and dry to obtain black PMMA@Ni / Ti3C2T x MXene nanosphere powder.

[0039] Step 2, Ni / Ti3C2T x Preparation of MXene porous composite films;

[0040] Step 2 is implemented as follows:

[0041] Take the concentration of 2mg / mL~4mg / mL Ti3C2T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of film was dried, PMMA@Ni / Ti3C2T was prepared according to step 1.2. x MXene nanosphere powder was dissolved in deionized water to prepare a dispersion with a concentration of 8 mg / mL to 16 mg / mL, and then 8 mg / mL to 16 mg / mL of PMMA@Ni / Ti3C2T x The MXene nanosphere dispersion was filtered through the second membrane. After the second layer of water was drained, the Ti3C2T x The MXene nanosheet dispersion was filtered for the third layer; the volume ratio of the three-layer filtrate was 1:1 to 4:1, and the entire film was taken out with the filter membrane after the water was drained, and then separated from the filter membrane after vacuum freeze drying for 20h to 28h, and PMMA@Ni / Ti3C2T x The MXene film was placed in a quartz boat, put into a tube furnace, and heated to 400°C-600°C at a heating rate of 2°C / min-5°C / min under Ar gas protection, and kept warm for 1h-3h. After cooling to room temperature, Ni / Ti3C2T x MXene porous composite film.

[0042] The present invention also provides a Ni nanoparticle-reinforced porous electromagnetic shielding film, which is prepared by the above method.

[0043] Example 1

[0044] Ni nanoparticles reinforced Ti3C2T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0045] Step 1, PMMA@Ni / Ti3C2T x Preparation of MXene nanospheres;

[0046] Step 1 is implemented as follows:

[0047] Step 1.1, preparation of PMMA / Ti3C2T x MXene nanosphere mixed solution:

[0048] PMMA nanospheres were dispersed in deionized water to prepare a 10 mg / mL dispersion and ultrasonically treated for 1 h.

[0049] Ti3AlC2 powder was etched by HCl / LiF, with a mass ratio of HCl, LiF and Ti3AlC2 of 30:2:1. The three were mixed and stirred in a constant temperature water bath for 24 h, and finally centrifuged and washed with deionized water until the solution pH = 6, thus obtaining Ti3C2T x MXene nanosheet dispersion.

[0050] Ti3C2T x After the MXene nanosheet dispersion was diluted to 2 mg / mL, 10 mL of the solution was taken into a beaker and 2 mL of 10 mg / mL PMMA nanosphere dispersion was slowly dripped into it. The mixture was ultrasonically treated in an ice bath for 20 min and magnetically stirred for 2 h to obtain PMMA / Ti3C2T x MXene nanosphere mixed solution.

[0051] In step 1.1, the size of the PMMA beads is 350 nm.

[0052] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti3C2T x MXene nanospheres:

[0053] Weigh 0.02 g NiCl2·6H2O and dissolve it in 10 mL anhydrous ethanol. Ultrasonicate for 20 min to mix evenly. Add the solution dropwise to the PMMA / Ti3C2T xAfter the solution was added, the mixture was stirred for 1 hour to obtain a mixed solution A. 5 g NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 20 minutes to fully dissolve it to obtain a mixed solution B. 10 mL N2H4·H2O was then quickly added to the mixed solution B and stirred for 20 minutes to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor and then subjected to a hydrothermal reaction in a drying oven at 120°C for 10 hours. After the reaction was completed, the black PMMA@Ni / Ti3C2T x MXene nanosphere powder.

[0054] Step 2, Ni / Ti3C2T x Preparation of MXene porous composite films.

[0055] Step 2 is implemented as follows:

[0056] Take 2mL of 2mg / mL Ti3C2T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, the PMMA@Ni / Ti3C2T prepared in step 1.2 was added. x MXene nanosphere powder was dissolved in deionized water to prepare a dispersion of 8 mg / mL, and then 5 mL of PMMA@Ni / Ti3C2T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 2 mL of 2 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and after vacuum freeze drying for 20 hours, PMMA@Ni / Ti3C2T was obtained by separating from the filter membrane. x MXene film. Place it in a quartz boat and put it into a tube furnace with Ar gas protection. Heat it to 400℃ at a heating rate of 2℃ / min and keep it warm for 1h. Cool it to room temperature and take it out to obtain Ni / Ti3C2T x MXene porous composite film.

[0057] Parameter 1: The diameter of the filtration membrane prepared in step 2 of Example 1 is 40 mm, and the filter membrane is a water-based mixed cellulose membrane with a pore size of 0.4 μm;

[0058] Parameter 2: Ni / Ti3C2T prepared in step 2 of Example 1 x The maximum electrical conductivity of MXene porous composite film is 234.8S / m;

[0059] Parameter 3: Ni / Ti3C2T prepared in step 2 of Example 1 xThe saturation magnetization Ms and coercive force Hc of the MXene porous composite film are 13.69emu / g and 77.38Oe, respectively;

[0060] Parameter 4: Ni / Ti3C2T prepared in step 2 of Example 1 x The electromagnetic shielding effectiveness of MXene porous composite film is 70.7dB.

[0061] Figure 1 The Ni / Ti3C2T prepared in Example 1 x MXene porous film and PMMA@Ni / Ti3C2T x XRD spectrum of MXene nanospheres. From the figure, it can be found that both samples have diffraction peaks at 44.3°, 51.7° and 76.1°, which are consistent with the standard PDF card of Ni (PDF#89-7128), corresponding to the (111), (200) and (220) crystal planes respectively. x The X-ray diffraction peak intensity of the MXene porous composite film is enhanced and the half-peak width is narrowed, indicating that the crystallinity of the Ni grains has been improved. x The 2θ angle of the (002) diffraction peak of MXene shifts to the left to 6.9°, indicating that the embedding of some Ni atoms increases the Ti3C2T x The interplanar spacing of MXene. No other peaks appear, indicating that x High-purity elemental Ni was successfully synthesized on MXene hollow nanospheres.

[0062] Figure 2 PMMA@Ni / Ti3C2T prepared in Example 1 x TEM image of MXene nanospheres. It can be seen from the figure that the nanospheres have a stable structure and a size of about 350nm.

[0063] Figure 3 The Ni / Ti3C2T prepared in Example 1 x SEM image of the cross section of the MXene porous composite film. As can be seen from the figure, the film thickness is about 20 microns, the layers are tightly bonded, and the middle is a typical hollow sphere structure.

[0064] Figure 4 for Figure 3 The enlarged image of the "A" area in the figure shows that the center of the composite film is a typical hollow sphere porous structure.

[0065] Figure 5 , Figure 6 , Figure 7 Ni / Ti3C2Tx The element distribution images of C, Ti and Ni elements in the MXene porous composite film show that the three elements are evenly distributed.

[0066] Example 2

[0067] Ni nanoparticles reinforced Ti3C2T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0068] Step 1, PMMA@Ni / Ti3C2T x Preparation of MXene nanospheres;

[0069] Step 1 is implemented as follows:

[0070] Step 1.1, preparation of PMMA@Ti3C2T by template method x MXene nanosphere mixed solution:

[0071] PMMA nanospheres were prepared into a 12 mg / mL dispersion and ultrasonically treated for 1.5 h.

[0072] Ti3AlC2 powder was etched using HCl / LiF. The mass ratio of HCl, LiF and Ti3AlC2 was 30:2:1. The three were mixed and stirred in a constant temperature water bath for 24 hours, and finally centrifuged and washed with deionized water until the solution pH = 6, thus obtaining Ti3C2T x MXene nanosheet dispersion.

[0073] After the nanosheet dispersion was diluted to 2.5 mg / mL, 2 mL of 12 mg / mL PMMA nanosphere dispersion was slowly dripped into 10 mL of the solution. The mixture was ultrasonically treated in an ice bath for 25 min and magnetically stirred for 3 h to obtain PMMA@Ti3C2T x MXene nanosphere mixed solution.

[0074] In step 1.1, the size of the PMMA beads is 300 nm.

[0075] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti3C2T x MXene nanospheres:

[0076] Weigh 0.03 g NiCl2·6H2O and dissolve it in 15 mL anhydrous ethanol. Ultrasonicate for 25 min to mix well. Add the solution dropwise to the PMMA / Ti3C2T xAfter the solution was added, the mixture was stirred for 1.5 hours to obtain a mixed solution A. 6 g of NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 25 minutes to fully dissolve it to obtain a mixed solution B. 15 mL of N2H4·H2O was then quickly added to the mixed solution B and stirred for 25 minutes to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor and then subjected to a hydrothermal reaction in a drying oven at 130°C for 11 hours. After the reaction was completed, the black PMMA@Ni / Ti3C2T x MXene nanosphere powder.

[0077] Step 2, Ni / Ti3C2T x Preparation of MXene porous composite films;

[0078] Step 2 is implemented as follows:

[0079] Take 2.5mL of 2.5mg / mL Ti3C2T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti3C2T was prepared according to step 1.2. x MXene nanosphere powder was dissolved in deionized water to prepare a 9 mg / mL dispersion, and then 5 mL of PMMA@Ni / Ti3C2T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 2.5 mL of 2.5 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and after vacuum freeze drying for 22 hours, it was separated from the filter membrane to obtain PMMA@Ni / Ti3C2T x MXene film. Place it in a quartz boat and put it into a tube furnace with Ar gas protection. Heat it to 500℃ at a heating rate of 3℃ / min and keep it warm for 1.5h. After cooling to room temperature in the furnace, Ni / Ti3C2T x MXene porous composite film.

[0080] Example 3

[0081] Ni nanoparticles reinforced Ti3C2T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0082] Step 1, PMMA@Ni / Ti3C2T x Preparation of MXene nanospheres;

[0083] Step 1 is implemented as follows:

[0084] Step 1.1, preparation of PMMA / Ti3C2T by template method x MXene nanosphere mixed solution:

[0085] PMMA nanospheres were prepared into a 14 mg / mL dispersion and ultrasonically treated for 2 h.

[0086] Ti3AlC2 powder was etched using HCl / LiF, with a mass ratio of HCl, LiF and Ti3AlC2 of 30:2:1. The three were mixed and stirred in a constant temperature water bath for 24 hours, and finally centrifuged and washed with deionized water until the solution pH = 6, thus obtaining Ti3C2T x MXene nanosheet dispersion.

[0087] After the nanosheet dispersion was diluted to 3 mg / mL, 2 mL of 14 mg / mL PMMA nanosphere dispersion was slowly dripped into 10 mL of the solution. The mixed solution was ultrasonically treated in an ice bath for 25 min and magnetically stirred for 4 h to obtain PMMA@Ti3C2T x MXene nanospheres mixed solution.

[0088] In step 1.1, the size of the PMMA beads is 400 nm.

[0089] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti3C2T x MXene nanospheres:

[0090] Weigh 0.04 g NiCl2·6H2O and dissolve it in 20 mL anhydrous ethanol. Ultrasonicate for 30 min to mix evenly. Add the solution dropwise to the PMMA / Ti3C2T x After the solution was added, the mixture was stirred for 2 hours to obtain a mixed solution A. 7 g NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 30 minutes to fully dissolve it to obtain a mixed solution B. Then 20 mL N2H4·H2O was quickly added to the mixed solution B and stirred for 30 minutes to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor and then subjected to a hydrothermal reaction in a drying oven at 140°C for 12 hours. After the reaction was completed, the black PMMA@Ni / Ti3C2T x MXene nanosphere powder.

[0091] Step 2, Ni / Ti3C2T x Preparation of MXene porous composite films.

[0092] Step 2 is implemented as follows:

[0093] Take 3mL of 3mg / mL Ti3C2Tx The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti3C2T was prepared according to step 1.2. x MXene nanosphere powder was dissolved in deionized water to prepare a 9 mg / mL dispersion, and then 6 mL of PMMA@Ni / Ti3C2T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 3 mL of 3 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and then vacuum-freeze-dried for 24 hours and then separated from the filter membrane to obtain PMMA@Ni / Ti3C2T x MXene film. Place it in a quartz boat and put it into a tube furnace with Ar gas protection. Heat it to 500℃ at a heating rate of 4℃ / min and keep it warm for 2h. After cooling to room temperature in the furnace, Ni / Ti3C2T x MXene porous composite film.

[0094] Example 4

[0095] Ni nanoparticles reinforced Ti3C2T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0096] Step 1, PMMA@Ni / Ti3C2T x Preparation of MXene nanospheres;

[0097] Step 1 is implemented as follows:

[0098] Step 1.1, preparation of PMMA / Ti3C2T by template method x MXene nanosphere mixed solution:

[0099] PMMA nanospheres were prepared into a 16 mg / mL dispersion and ultrasonically treated for 2.5 h.

[0100] Ti3AlC2 powder was etched using HCl / LiF. The mass ratio of HCl, LiF and Ti3AlC2 was 30:2:1. The three were mixed and stirred in a constant temperature water bath for 24 hours, and finally washed with deionized water until the solution pH = 6, thus obtaining Ti3C2T x MXene nanosphere dispersion.

[0101] Ti3C2T x After the MXene nanosheet dispersion was diluted to 3.5 mg / mL, 2 mL of 16 mg / mL PMMA nanosphere dispersion was slowly dripped into 10 mL of the solution. The mixture was ultrasonically treated in an ice bath for 35 min and magnetically stirred for 5 h to obtain PMMA@Ti3C2Tx MXene nanosphere mixed dispersion.

[0102] In step 1.1, the size of the PMMA beads is 500 nm.

[0103] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti3C2T x MXene nanospheres:

[0104] Weigh 0.04 g NiCl2·6H2O and dissolve it in 25 mL anhydrous ethanol. Ultrasonicate for 35 min to mix evenly. Add the solution dropwise to the PMMA / Ti3C2T x After the solution was added, the mixture was stirred for 2.5 hours to obtain a mixed solution A. 8 g NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 35 minutes to fully dissolve it to obtain a mixed solution B. 25 mL N2H4·H2O was then quickly added to the mixed solution B and stirred for 35 minutes to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor and then subjected to a hydrothermal reaction in a drying oven at 150°C for 13 hours. After the reaction was completed, the black PMMA@Ni / Ti3C2T x MXene nanosphere powder.

[0105] Step 2, Ni / Ti3C2T x Preparation of MXene porous composite films.

[0106] Step 2 is implemented as follows:

[0107] Take 3.5mL of 3.5mg / mL Ti3C2T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti3C2T was prepared according to step 1.2. x MXene nanosphere powder was dissolved in deionized water to prepare a 10 mg / mL dispersion. Then 5 mL of PMMA@Ni / Ti3C2T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 3.5 mL of 3.5 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and after vacuum freeze drying for 26 hours, it was separated from the filter membrane to obtain PMMA@Ni / Ti3C2T x MXene film. Place it in a quartz boat and put it into a tube furnace with Ar gas protection. Heat it to 550℃ at a heating rate of 5℃ / min and keep it warm for 2.5h. After cooling to room temperature in the furnace, Ni / Ti3C2T xMXene porous composite film.

[0108] Example 5

[0109] Ni nanoparticles reinforced Ti3C2T x The preparation method of the MXene porous electromagnetic shielding film specifically comprises the following steps:

[0110] Step 1, PMMA@Ni / Ti3C2T x Preparation of MXene nanospheres;

[0111] Step 1 is implemented as follows:

[0112] Step 1.1, preparation of PMMA / Ti3C2T by template method x MXene nanosphere mixed solution:

[0113] PMMA nanospheres were prepared into a dispersion of 18 mg / mL and ultrasonically treated for 3 h.

[0114] Ti3AlC2 powder was etched using HCl / LiF. The mass ratio of HCl, LiF and Ti3AlC2 was 30:2:1. The three were mixed and stirred in a constant temperature water bath for 24 hours, and finally centrifuged and washed with deionized water until the solution pH = 6, thus obtaining Ti3C2T x MXene nanosheet dispersion.

[0115] Ti3C2T x After the MXene nanosheet dispersion was diluted to 4 mg / mL, 2 mL of 20 mg / mL PMMA nanosphere dispersion was slowly dripped into 10 mL of the solution. The mixture was ultrasonically treated in an ice bath for 40 min and magnetically stirred for 5 h to obtain PMMA@Ti3C2T x MXene nanosphere mixed dispersion.

[0116] In step 1.1, the size of the PMMA beads is 600 nm.

[0117] Step 1.2, hydrothermal preparation of PMMA@Ni / Ti3C2T x MXene nanospheres:

[0118] Weigh 0.04 g NiCl2·6H2O and dissolve it in 30 mL anhydrous ethanol. Ultrasonicate for 40 min to mix evenly. Add the solution dropwise to the PMMA / Ti3C2T xAfter the solution was added, the mixture was stirred for 3 hours to obtain a mixed solution A. 8 g NaOH was weighed and added to the mixed solution A, and then stirred in an ice bath for 40 minutes to fully dissolve it to obtain a mixed solution B. 30 mL N2H4·H2O was then quickly added to the mixed solution B and stirred for 40 minutes to obtain a mixed solution C. The fully stirred mixed solution C was placed in a stainless steel reactor and then subjected to a hydrothermal reaction in a drying oven at 150°C for 15 hours. After the reaction was completed, the black PMMA@Ni / Ti3C2T x MXene nanosphere powder.

[0119] Step 2, Ni / Ti3C2T x Preparation of MXene porous composite films.

[0120] Step 2 is implemented as follows:

[0121] Take 4 mL of 4 mg / mL nanosheet dispersion for the first layer of suction filtration. After the first layer of water is drained, the PMMA@Ni / Ti3C2T prepared in step 1.2 is filtered. x MXene nanosphere powder was dissolved in deionized water to prepare a dispersion of 8 mg / mL, and then 8 mL of PMMA@Ni / Ti3C2T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer was drained, 4 mL of 4 mg / mL nanosheet dispersion was taken for the third layer. After the entire film was drained, it was taken out with the filter membrane, and after vacuum freeze drying for 28 hours, PMMA@Ni / Ti3C2T was obtained by separating from the filter membrane. x MXene film. Place it in a quartz boat and put it into a tube furnace with Ar gas protection. Heat it to 600℃ at a heating rate of 5℃ / min and keep it warm for 3h. Cool it to room temperature and take it out to obtain Ni / Ti3C2T x MXene porous composite film.

[0122] After measurement and analysis, Ti3C2T with multiple interface structures and dual-component systems was successfully prepared. x MXene-based composite materials; After measurement and analysis, each embodiment successfully prepared Ni / Ti3C2T with Ni nanoparticles as the reinforcing phase in the porous film x MXene composite films.

[0123] The electromagnetic parameters of the composite material in the X-band (8.2-12.4 GHz) were measured using a network vector analyzer, and the total electromagnetic shielding effectiveness was calculated. The results are shown in Table 1. The conductivity data of the corresponding materials are also recorded in Table 1.

[0124] Table 1

[0125] Total electromagnetic shielding effectiveness (dB) Conductivity (S / m) Example 1 70.7 234.8 Example 2 73.2 245.7 Example 3 75.9 259.1 Example 4 76.6 270.2 Example 5 77.4 320.5 <![CDATA[Ti3C2T x MXene film]]> 32.21 178.3

[0126] The present invention uses porous Ti3C2T x Ni / Ti3C2T was prepared with MXene as the matrix and Ni nanoparticles as the reinforcement. x MXene porous composite film. Ni nanoparticles and Ti3C2T x The synergistic effect of MXene performance and the optimization of impedance matching by porous structure have achieved the goal of Ti3C2T x Enhanced electromagnetic shielding properties of MXene.

[0127] The method of the present invention can be carried out by Ti3C2T x The synergistic effect of MXene dielectric loss and Ni nanoparticle magnetic loss, as well as the impedance matching optimization caused by the porous structure, results in the Ni / Ti3C2T with high electromagnetic shielding effectiveness. x MXene porous composite film. It can be seen from Table 1 that the electromagnetic shielding performance of the composite film of the present invention is excellent, which is far higher than the performance requirements of commercial electromagnetic shielding materials. x Compared with the composite film of the present invention, the magnetism and conductivity of MXene are also significantly improved.

[0128] When the electromagnetic shielding capability is improved, the conductivity of this system can reach 234.8 to 320.5 (S / m). x The method of MXene electromagnetic shielding composite material has the characteristics of simple manufacturing process and good stability. The thickness of the prepared porous composite film is between 20 and 60 μm, and the electromagnetic shielding efficiency in the X-band can reach up to 70.7 dB to 77.4 dB.

Claims

1. A method for preparing a Ni nanoparticle-reinforced porous electromagnetic shielding film, characterized in that: The specific steps include: Step 1, PMMA@Ni / Ti3C2T x Preparation of MXene nanospheres; Step 2, Ni / Ti3C2T x Preparation of MXene porous composite films.

2. The method for preparing the Ni nanoparticle-reinforced porous electromagnetic shielding film according to claim 1, characterized in that: Step 1 is implemented as follows: Step 1.1, preparation of PMMA / Ti3C2T by template method x MXene nanosphere mixed solution: First, a PMMA nanosphere dispersion with a concentration of 10 mg / mL to 20 mg / mL was prepared, and ultrasonic treatment was performed for 1 h to 3 h. Then, a Ti3C2T x MXene nanosheet dispersion; Ti3C2T x The MXene nanosheet dispersion was slowly dripped into the PMMA nanosphere dispersion, and PMMA and Ti3C2T in the mixed solution x The mass ratio of MXene nanosheets was 1:1-2, and the mixed solution was ultrasonically treated in an ice bath for 20-40 min and magnetically stirred for 2-5 h to obtain PMMA / Ti3C2T x MXene nanosphere mixed solution; Step 1.2, hydrothermal preparation of PMMA@Ni / Ti3C2T x MXene nanospheres: Dissolve NiCl2·6H2O in anhydrous ethanol to prepare a solution with a concentration of 0.6 mg / mL to 4 mg / mL, treat with ultrasound for 20 min to 40 min to mix evenly, and then drop the solution into the PMMA / Ti3C2T x In the MXene nanosheet mixed solution, after the solution is added dropwise, stirring is continued for 1h to 3h to obtain a mixed solution A, NaOH is added to the mixed solution A, the concentration of NaOH in the mixed solution A is 0.5g / mL to 0.8g / mL, and then stirred in an ice bath for 20min to 40min to fully dissolve it to obtain a mixed solution B; N2H4·H2O is then added dropwise to the mixed solution B, the volume ratio of N2H4·H2O to anhydrous ethanol is 1:1 to 3, and stirred for 20min to 40min to obtain a mixed solution C, and the fully stirred mixed solution C is placed in a stainless steel reactor, and then a hydrothermal reaction is carried out in a drying oven at 120℃ to 150℃ for 10h to 15h. After the reaction is completed, PMMA@Ni / Ti3C2T x MXene nanosphere powder.

3. The method for preparing the Ni nanoparticle-reinforced porous electromagnetic shielding film according to claim 1, characterized in that: In step 1.1: the size of PMMA nanospheres is 200nm~600nm; Ti3C2T x MXene nanosheets were prepared from Ti3AlC2 powder by chemical etching, with HCl / LiF as the etchant.

4. The method for preparing the Ni nanoparticle-reinforced porous electromagnetic shielding film according to claim 1, characterized in that: Step 2 is implemented as follows: Take the concentration of 2mg / mL~4mg / mL Ti3C2T x The MXene nanosheet dispersion was filtered for the first layer. After the first layer of water was drained, PMMA@Ni / Ti3C2T was prepared according to step 1.

2. x MXene nanosphere powder was dissolved in deionized water to prepare a dispersion with a concentration of 8 mg / mL to 16 mg / mL, and then 8 mg / mL to 16 mg / mL of PMMA@Ni / Ti3C2T x The MXene nanosphere dispersion was filtered for the second layer, and after the second layer of water was drained, Ti3C2T x The MXene nanosheet dispersion was filtered for the third layer; the volume ratio of the three-layer filtrate was 1:1 to 4:1, and the entire film was taken out with the filter membrane after the water was drained, and then separated from the filter membrane after vacuum freeze drying for 20h to 28h, and PMMA@Ni / Ti3C2T x The MXene film was placed in a quartz boat, put into a tube furnace, and heated to 400°C-600°C at a heating rate of 2°C / min-5°C / min under Ar gas protection, and kept warm for 1h-3h. After cooling to room temperature, Ni / Ti3C2T x MXene porous composite film.

5. Ni nanoparticle-enhanced porous electromagnetic shielding film, characterized in that: The method is prepared by any one of claims 1 to 4.

Citation Information

Patent Citations

  • MXene / Ni composite material as well as preparation method and application thereof

    CN112225220A

  • MXene microsphere composite wave-absorbing material modified by spiny Ni elementary substance as well as preparation and application of MXene microsphere composite wave-absorbing material

    CN114390880A

  • MXene-rGO composite film and preparation method and application thereof

    CN116437651A

  • MXene flexible thin film with metal nickel doped porous structure and preparation method and application of MXene flexible thin film

    CN118524693A

  • Transition metal carbonitride mxene films for EMI shielding

    US20210261415A1